Law and Crisis: Reflections on How Legal Problems Are Constructed and How They Can Be Studied - Johanna Niemi (Jurist- og Økonomforbundets Forlag, 2022)
Using the social construction of crises as a starting point the article draws a parallel between construction of a crisis and a legal problem. The question how legal problems are constructed has not received much attention in legal theory. Within theories of social constructionism Carol Bacchi’s What’s the problem approach provides a basis to study how legal problems are constructed in the legal texts, practices and discourses. Contrasting rational legal argumentation theory and social constructionism the article argues that the latter allows a reflection between different problem formulations and interpretations. Discourse analysis is proposed as a method for such analysis.